2012
DOI: 10.1109/tbme.2012.2196275
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hemodynamically Optimal Coronary Stent Designs Based on Vessel Caliber

Abstract: Coronary stent design influences local patterns of wall shear stress (WSS) that are associated with neointimal growth, restenosis, and the endothelialization of stent struts. The number of circumferentially repeating crowns NC for a given stent de-sign is often modified depending on the target vessel caliber, but the hemodynamic implications of altering NC have not previously been studied. In this investigation, we analyzed the relationship between vessel diameter and the hemodynamically optimal NC using a der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…These tools have potential for clinical impact and have been used in optimizing coronary stent design [3] thrombotic risk stratification for Kawasaki disease [4, 5], analyzing the correlation between wall shear stress and atherosclerosis [6], and non-invasive assessment of fractional flow reserve [7]. …”
Section: Introductionmentioning
confidence: 99%
“…These tools have potential for clinical impact and have been used in optimizing coronary stent design [3] thrombotic risk stratification for Kawasaki disease [4, 5], analyzing the correlation between wall shear stress and atherosclerosis [6], and non-invasive assessment of fractional flow reserve [7]. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous studies have reported the optimization of stent strut geometry with the goal of minimizing blood flow disturbance in the arterial lumen [1215], stresses in the stent itself [16], or stresses in the arterial wall [17]. Pant and collaborators recently reported the first attempt at including multiple design objectives and multiple physical phenomena in the optimization process with the use of a steady (time-independent) transport model to investigate the effect of DES geometric design on the homogeneity of drug distribution and its average concentration in the arterial wall [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…While regulatory requirements have certainly been met for these stents, their design attributes may not have been optimized in the strictest sense of the word. For example, we recently showed intrastrut hemodynamics are only optimized over a small range of diameters for one FDA‐approved stent studied using idealized models . Modifying the stent sizing matrix could extend this finding over a greater range of diameters and engineering metrics of interest .…”
Section: Introductionmentioning
confidence: 98%